American Committee Of Engineers In London (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1917)
A letter has been received by the Secretary of the Institute from Mr. C. W. Purington, Honorary. Secretary of the. American Committee of Engineers in London, whose offices are at 6, Copthall Avenue, London, E. C. 2, which will be of interest to any member who may be intending to go to England. Mr. Purington says: "A Committee of Americans has been formed here, consisting mostly of Mining Engineers, and those interested-in mining and allied industries. We should be very glad, among other duties, to give assistance to any American engineers arriving in England on official business connected with the war. This assistance would probably take the form of offering advice and hints as to saving time in approaching British official Departments, and generally in getting. about." This Committee of Engineers was organized with the approval of the American Ambassador to Great Britain, who has recommended its services to the United States Government in connection with the conduct of the war.